Virtual On-Premise Shopping System with Face Recognition Authentication - Yap, Choi Sen; Cheng, Chee Chen Dandy (INTI International University, 2022)
This project aims to develop a modern, convenient, and secure virtual on-premise shopping system to promote efficient shopping with minimal waste. The system provides users with the ability to shop and pick up purchased items with minimal effort, which is particularly helpful for elders who are unable to carry heavy items for long periods. This system consists of an E-catalogue to enable product browsing, as well as a mobile app to enable the shopping process. With the proposed system, consumers are only required to sign up for an account to begin the process. After a topup, consumers can simply start adding items to their virtual shopping cart by scanning any QR code on the E-catalogue. To ensure account and data security, consumers can simply opt-in face recognition upon signing up to enable two-factor authentication (2FA) to ensure that account security is not compromised. With the admin panel in place, the relevant staff will be able to easily modify item prices, and categories, manage stock and create purchase orders. Furthermore, the packaging department will be able to take advantage of the system to keep track of consumers’ purchased items and notify consumers upon the completion of the packaging process.